a comparison of deuterium oxide dilution and maternal weighing methods for estimating sow milk yield - S. Prowirodigdo; R.H. King; A.C. Dunkin; P.E. Hughes; H. Dove (Hemera Zoa, 1992)
The D2O dilution technique was used to accurancy